Phage heterogeneity of coagulase-negative staphylococci isolated in the United States and Sweden from bovine milk. - Holmberg, O (1979)
A Swedish bovine and a Dutch human phage set for coagulase-negative staphylococci were used to phage type coagulase-negative staphylococci isolated from bovine milk from Minnesota dairy herds. A comparison was also made of the deoxyribonuclease activity of coagulase-negative staphylococci isolated from bovine milk in Sweden and Minnesota. Of 133 Minnesota isolates, only one could be typed with the Swedish set and one by the Dutch set, whereas of 218 Swedish strains, 49 could be typed with the Swedish set and 7 by the Dutch set. A larger number of coagulase-negative isolates from Sweden were deoxyribonuclease positive (35%) than were the similar isolates from Minnesota (12%). These findings substantiate the marked heterogeneity of coagulase-negative staphylococci isolated from bovine udders. Results presented point to the usefulness of establishing regional phage sets for epidemiological investigations of coagulase-negative staphylococci in cattle. It is anticipated that at a later stage the regional phage sets will be coordinated internationally.